Controlled Cost: An Operational Concept and Statistical Approach to Standard Costing. - Luh, F. S. (The Accounting Review, 1968)
The article proposes a refinement of standard cost, to be called "controlled cost," using statistical techniques to evaluate operating efficiency and degree of control. The primary usefulness of a standard cost system is to facilitate cost control through identification of situations and investigation of performance when actual cost deviates significantly from standard cost. A level of cost that should be attained under efficient operation is specified and then compared with actual cost to measure operating efficiency and degree of control. Present practices of standard costing are based primarily on an assumption that the expected value of an efficient operation is stability and that any significant deviation of the mean of actual cost from the expected value indicates abnormality of operation requiring managerial attention. Earlier works of cost accountants have extended the concept of standard cost from a single value comparison to a range of control limits. A range of costs is established by statistical control techniques, and when actual costs fall outside the control limits, managerial investigation is required.